Chemoradiation in rectal squamous cell carcinoma: Bi-institutional case series. (May 2016) - Loganadane, Gokoulakrichenane; Servagi-Vernat, Stéphanie; Schernberg, Antoine; Schlienger, Michel; Touboul, Emmanuel; Bosset, Jean-François; Huguet, Florence
Abstract: Background and purpose: Primary rectal squamous cell carcinoma (SCC) is an uncommon disease. Early reports stated that surgery is the most effective treatment. However, recent publications suggest conservative strategy with chemoradiation provides satisfactory results. Patients and methods: We have retrospectively studied the medical charts of 23 patients treated for a rectal SCC in two teaching hospitals in France between 1992 and 2013. Twenty-one patients received an exclusive chemoradiotherapy (CRT) and two a pre-operative CRT followed by a planned surgery. Patients received pelvic irradiation with a dose ranging from 36–45 Gy followed by a boost of 15–23 Gy. Twenty-two patients received a concurrent chemotherapy. Results: After CRT, the rate of clinical complete response was 83%. With a median follow-up of 85 months, 5-year overall survival rate was 86%. Five patients presented with a relapse. The 5-year disease-free survival rate was 81%. The 5-year colostomy-free survival rate was 65%. Three patients (13%) presented with grade III–IV late rectal toxicity. Conclusions: Although retrospective, this is the largest cohort of patients treated with CRT for a rectal SCC. Exclusive CRT could result in high local control rate and prolonged survival in rectal SCC patients with a high rate of organ preservation. Highlights: Primary rectal squamous cell carcinoma (SCC) is an uncommon disease. Our series includes 23 patients treated for a rectal SCC in two teaching hospitals in France. After chemoradiotherapy, the rate of clinical complete response was 83% and 5-year three patients (13%) presented with grade III–IV late rectal toxicity. Exclusive chemoradiotherapy could result in high local control rate and prolonged survival in rectal SCC patients with a high rate of organ preservation.